News - Eva M. Riedmann (Human Vaccines & Immunotherapeutics)
Successful combination: existing drugs boost cancer vaccine responsesInovio's universal avian flu vaccine generates protective antibody responses in phase 1Update on NewLink’s HyperAcute cancer immunotherapy productsGhana and Rwanda expand national immunization programsNews studies: Combining PROSTVAC with conventional cancer therapyPromising phase 1 data for the first "Cross-Kingdom“ vaccine Oral TB vaccine shows promise in phase 2 trial